Quality assurance manual: Academic programme collaboration - Azle, Abd Ghalim; Azri, Alias; Azrizulazmi, Bustan; Fadzida, Ismail; Hamdan, Daniyal; Hamzah, Ahmad; Mahfuzah, Mustafa; Mohamad Fadli, Zolkipli; Mohamad Rusydi, Mohamad Yasin; Mohd Azmir, Mohd Azhari; Mohd Fadzil Faisae, Ab Rashid; Mohd Fairusham, Ghazali; et al. (Penerbit UMP, 2018)
I the Name of Allah, the Most Gracious and the Most Merciful. Praise be to Allah, the Lord of the Universe. Peace and blessings on Prophet Muhammad, the messenger of God. The objective of developing this quality assurance manual for academic programme collaboration of Universiti Malaysia Pahang (UMP) is to guide the operation of academic collaboration between UMo and other institutions of higher education. The manual is in tandem with the calture of Qualiti Management Sysytems towards delivering high quality academic programmes and graduates according to the vision and mission of the university. The manual is in the family of CAIC series under Quality Assurance Manual.